2018
DOI: 10.14742/ajet.3548
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between English language learners’ online self-regulation and their self-efficacy

Abstract: This quantitative study investigated the relationship between learners' online self-regulation and their self-efficacy in the context of learning English as a foreign language (EFL). We collected data from two surveys, the online self-regulated English learning (OSEL) and the English language self-efficacy (ELSE), among 424 university students in China. Principal component analyses showed that the OSEL included six sub-scales, namely, goal setting, environment structuring, task strategies, time management, hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 66 publications
2
44
0
Order By: Relevance
“…Learners with stronger sense of efficacy also displayed greater persistence and engagement through regulating their own language learning process and using a greater range of strategies appropriately (Sardegna, Lee, & Kusey, ). Similarly, learners with higher English proficiency perceived themselves more capable of self‐evaluating learning processes, structuring the learning environment, and setting instructional goals among learners (Su et al., ). Those findings, which were questionnaire‐based, consistently suggest the interplay between EFL learners’ self‐regulated learning abilities and their self‐efficacy.…”
Section: Self‐efficacy Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Learners with stronger sense of efficacy also displayed greater persistence and engagement through regulating their own language learning process and using a greater range of strategies appropriately (Sardegna, Lee, & Kusey, ). Similarly, learners with higher English proficiency perceived themselves more capable of self‐evaluating learning processes, structuring the learning environment, and setting instructional goals among learners (Su et al., ). Those findings, which were questionnaire‐based, consistently suggest the interplay between EFL learners’ self‐regulated learning abilities and their self‐efficacy.…”
Section: Self‐efficacy Beliefsmentioning
confidence: 99%
“…They can affect how much learners are cognitively and motivationally engaged in the course of learning (Linnenbrink & Pintrich, ). Studies have suggested that learners with a strong sense of self‐efficacy are more self‐regulated (Mizumoto, ; Su, Zheng, Liang, & Tsai, ), more task‐centered, and less anxious of possible failures (Al‐Harthy, Was, & Isaacson, ; Usher & Pajares, ). These learners also tend to show more effort and display positive attitude and persistence in coping with difficult tasks (Komarraju & Nadler, ; Woodrow, ).…”
Section: Introductionmentioning
confidence: 99%
“…There was also a strong relationship between students' self-regulation and their language learning strategies in Erdogan's study (2017). In addition, there was a positive correlation between students' self-efficacy and their online self-regulation in the study of Su, Zheng, Liang and Tsai (2018). On the other hand, some research had uncertain findings of the relationship between self-regulated learning strategies and foreign language classroom anxiety such as Martirossian and Hartoonian (2015) and between self-regulated learning and the prediction of students' GPA e.g.…”
Section: Performance Phasementioning
confidence: 94%
“…The verification of these strategies in the context of student experience of LDGM has practical implications. Environmental structuring (Kocdar et al, 2018;Su, Zheng, Liang, & Tsai, 2018;Zimmerman, 2008) has been identified in a range of contexts as an important self-regulation strategy. In this study, environmental structuring focused on students choosing times and locations in which to work on their digital media assignments.…”
Section: Implications Of the Studymentioning
confidence: 99%